2016
DOI: 10.1111/irv.12432
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of influenza B in Australia: 2001‐2014 influenza seasons

Abstract: BackgroundInfluenza B is characterised by two antigenic lineages: B/Victoria and B/Yamagata. These lineages circulate together with influenza A during influenza seasons, with varying incidence from year to year and by geographic region.ObjectiveTo determine the epidemiology of influenza B relative to influenza A in Australia.MethodsLaboratory‐confirmed influenza notifications between 2001 and 2014 in Australia were obtained from the Australian National Notifiable Diseases Surveillance System.ResultsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
9
35
2
Order By: Relevance
“…During the influenza seasons, where influenza B was predominant (2012‐2013 season) or presented at a late peak of activity (2014‐2015 and 2015‐2016 influenza seasons), we found that the 5‐14 age‐group was considerably more affected compared to other influenza seasons. This finding was also described in other countries in Europe and in Australia 22, 23, 24. In children younger than 5 years, it is more difficult to find a virus‐specific pattern regarding the influenza disease burden.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…During the influenza seasons, where influenza B was predominant (2012‐2013 season) or presented at a late peak of activity (2014‐2015 and 2015‐2016 influenza seasons), we found that the 5‐14 age‐group was considerably more affected compared to other influenza seasons. This finding was also described in other countries in Europe and in Australia 22, 23, 24. In children younger than 5 years, it is more difficult to find a virus‐specific pattern regarding the influenza disease burden.…”
Section: Discussionsupporting
confidence: 74%
“…This finding was also described in other countries in Europe and in Australia. [22][23][24] In children younger than 5 years, it is more difficult to find a virus-specific pattern regarding the influenza disease burden. We found a high disease burden in seasons dominated by A(H1N1) (2015-2016), but also in A(H3N2) dominant as the 2011-2012 influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…Following duplicate removal (N = 946) and the screening of titles and abstracts (N = 5787), a total of 43 records were deemed to be worthy of further evaluation and the corresponding full texts were assessed. Of these, 16 papers met all inclusion criteria and were included. In the study by Caini et al only 12 of 26 study locations had a sufficient number (≥100) of isolates among the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive literature search was conducted; this included both automatic and manual modalities. As the authors of this study were aware that several studies on the outcomes of interest were available, the automatic search strategy was constructed in several steps until all known studies appeared among the search results. To do this, it was first assumed that studies reporting the frequency of IVB would also report that of IVA.…”
Section: Methodsmentioning
confidence: 99%
“…We did not show uncertainty intervals for prediction results of DNN models, but the 95% confidence interval for prediction of ARIMAX were shown in S7 Fig. Furthermore, we included only data from laboratory-confirmed cases, which may underestimate the true incidence of influenza in the population [27]. Further research with inter-US geographic scales for US Health and Human Services regions is warranted to analyze detail scales to find matched country with similar pattern of influenza surveillance.…”
Section: Discussionmentioning
confidence: 99%